Simulation of the processes of the electrons transfer in the semiconductor structure based on graphene - V. V. Murav'ev; V. N. Mishchenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of modeling of electron transfer processes in a three-dimensional semiconductor structure containing a single layer of graphene using the Monte-Carlo method are presented. The use of graphene, which has a high mobility of charge carriers, high thermal conductivity and a number of other positive properties, is promising for the creation of new semiconductor devices with good output characteristics . As a result of modeling, the dependences of the velocity, average energy, mobility, diffusion coefficient on the structure length and electric field intensity in a semiconductor structure containing a graphene layer and a region of a 4H-SiC silicon carbide material are obtained.